PERILAKU SEKSUAL REMAJA DALAM PENCEGAHAN HIV/AIDS DI KAMPUNG BANTEN PASAR VIII KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2016 - Mahardika Aisyiyah Nasution (Universitas Prima Indonesia, 2018)
Adolescent sexual behavior in the prevention of Human Immuno Deficiency Virus (HIV)/Acquired Immuno Deficiency Syndrome (AIDS) is every behavior driven by sexual desire, both with the opposite sex or the same sex in preventing HIV/AIDS. Prevention ofHIV/AIDS here includes Abstinence, Be Faithful, Condom, Drugs and Eqiupment. The purpose of this study was to explore in depth the sexual behavior of adolescents in the prevention of HIV/AIDS in Kampung Banten Pasar VIII Subdistrict of Tanjung Morawa District of Deli Serdang. This study is a qualitative research with technique of data collecting through interview, observation and documentation as well as the validity of the data using triangulation. The results showed that the informant more quickly obtain information from peers and media. The knowledge of adolescents about the prevention of HIV/AIDS throughout the informant knew though not in depth. Adolescent attitude toward sexual behavior did not agree to reveal their affection without physical contact and sexual intercourse, whereas adolescents practice in the prevention of HIV/AIDS is still not applied and all informants were not doing prevention of HIV/AIDS (abstinence, be faitful, condom, drugs unless equipment) Suggested to adolescent not to make sexual intercouse before marriage, Suggested to peer informant to fill the time with positive activities, it is suggested to all creators media both electronic and otherwiseto further restrict what can be published,it is necessary liveliness health workers in handling problems of teenagers to better embrace the youth in order to learn more about healthy sex, sexual behaviors and their consequences and prevention of HIV/AIDS and the need for education to parents who have teenagers to provide sex education at an early stage as a teenager in her social guidelines